Lichen Simplex Chronicus as an Essential Part of the Dermatologic Masquerade - Voicu, Cristiana (Open Access Maced J Med Sci, 2017)
A 48 years old female patient had been suffering from the lesions presented for four years. They have started as small, pruritic patches which had been mechanically irritated and grew up in time. The patient had no associated comorbidities or allergies, and she was not under any medication. On physical examination, she presented one erythematous, exudative plaque, with dimensions of 2.5/4 cm, located on the proximal phalanx and interphalangeal articulation of the left thumb. All histopathological features were consistent with the diagnosis of lichen simplex chronicus. Some lesions of lichen simplex chronicus exhibit signs of pseudocarcinomatous, infundibular and sometimes eccrine ductal proliferation of keratinocytes. Although the pseudoinfiltrative aspect of the epithelial proliferation and its pronounced degree might mimic a well-differentiated lesion of squamous cell carcinoma, a lack of cellular atypia and atypical mitotic figures are features that do not support this diagnosis. On the other hand, long lasting lesions of lichen simplex chronicus may lead to alterations in the processes of keratinocyte proliferation and differentiation and eventually give rise to malignant transformation. The best treatment management is a psychodermatological approach, a combination of skin care with psychotherapy, in order to prevent relapses.